EPS Analysis and Phytostimulatory Potential of Biofilm-forming Bacteria - Bibi, Naseem; Ahmed, Ambreen; Tariq, Aqsa (BioScientific Review, 2026)
Use of plant growth-promoting rhizobacteria (PGPR) reclaims the productivity of the agricultural land through several mechanisms. Biofilm-forming rhizobacteria secrete extracellular polymeric substances (EPS) embedded in their self-produced exopolysaccharides. In the current study, thirty-seven isolates were evaluated or auxin production ability, however, ten isolates displayed significant auxin production ability. Six out of these ten isolates were biofilm-forming rhizobacteria, that is, Pseudomonas sp. 1 (DS1), Shewanella putrefaciens (DS2), Pseudomonas sp. 2 (DS3), Pseudomonas aeruginosa (DS4), Sporosarcina saromensis (E1), and B3. These were analyzed for their EPS production ability. The EPS production capacity of these rhizobacteria was evaluated under various physiological attributes, such as temperature, pH, and incubation periods. Phytostimulatory potential of the rhizobacterial strains was evaluated using Zea mays L. with monoculture and co-culture conditions. Results indicated that bacterial strains significantly enhanced the growth parameters, such as the percentage germination, shoot length, root length, number of leaves as well as fresh weight and biochemical parameters, that is, chlorophyll and soluble protein content of the plants. Distinct from previous PGPR studies, this study is unique in the evaluation of six rhizobacterial isolates with respect to the EPS production ability under varied pH, temperature, and incubation conditions and their combined effects in consortia in correlation with phytostimulatory impacts on Zea mays L. Thus, the EPS producing bacteria can be used as a sustainable biofertilizer to promote plant growth.